Long term effect of feeding spray dried plasma during the nursery on subsequent performance and health status to market weight - da Silva, Caio Abércio; de Souza, Kelly Lais; Dias, Cleandro Pazinato; Callegari, Marco Aurélio; Crenshaw, Joe; Polo, Javier; Rangel, Luis; Shen, Yanbin; de Carvalho, Rafael Humberto (Frontiers in Veterinary Science, 2025)
Spray-dried plasma (SDP) is widely used in nursery pig diets due to nutritional and functional benefits, including improved feed intake, gut health, and immune modulation. Although its short-term effects are well documented, its long-term impact on growth and health until market weight remains unclear. We evaluated the effects of increasing SDP inclusion levels during the nursery phase on subsequent performance, health status, and carcass traits in pigs. A total of 300 weaned piglets (PIC® Camborough × AG 415) were randomly allocated to five dietary treatments with cumulative SDP intakes, differing in cumulative SDP intake: control (CON), 0 g SDP; low (L-SDP), 85 g; medium (M-SDP), 180 g; high (H-SDP), 340 g; and very high (VH-SDP), 610 g. Pigs were monitored across nursery, growing, and finishing phases. During the nursery, SDP inclusion had no effect on average daily feed intake (ADFI), average daily gain (ADG), feed conversion rate (FCR), or final body weight (FBW). However, pigs receiving SDP diets showed reduced diarrhea severity (p < 0.05) and required fewer medical interventions for gastrointestinal disorders (p < 0.05). In the grow-finish phase, regression analysis revealed a linear increase in ADFI (p = 0.074), ADG (p = 0.062), and FBW (p = 0.037) at slaughter with higher nursery SDP intake. Carcass trait evaluation indicated that increasing nursery SDP intake was associated with an increase in backfat thickness (p = 0.052) and a reduction in carcass lean percentage (p = 0.039), although lean meat yield (kg) was not different among treatments. Importantly, all SDP-fed groups exhibited a lower lung pneumonia index at slaughter compared with the control (p < 0.001). These results support the strategic use of SDP in nursery diets, aiming to promote subsequent health and performance up to commercial slaughter age.